Die Paasfeesviering van die Henogitiese Quartadecimane in die eerste drie eeue van die Christendom - Wilhelm Pretorius (Verbum et Ecclesia, 2019)
The celebration of the Passover of the Enoochite Quatradecimans during the first three centuries of Christianity. Development concerning the determination of Passover or Pascha’s annual date took place during the first three centuries of Christianity. This led to a controversy in the mid-second century AD which became known as the Quartadecima Controversy. The date and duration of the Passover were the main issues. During the controversy two main streams emerged, namely the Quartadecimans and Anti-Quartadecimans. The Quartadecimans celebrated the 14th of the first month annually as the commencement date of the Passover. The Anti-Quartadecimans set the first or second weekend after the 14th of the first month annually as the Passover celebration date. In spite of the two main streams, commonly accepted by modern-day researchers, various variations developed within these two main streams. These variations have not been discerned and analysed in modern-day research. One of these variations, namely the Enochite Quatradecimans is the subject of this article. They are being portrayed as a unique and discernable variation within the Quartadeciman main stream. Intradisciplinary and/or interdisciplinary implications: This article connects the research fields of New Testament and Church History in trying to understand how and when the Passover was celebrated during the first three centuries of Christianity.